Search of ways to menopausal hormonal therapy and correction of bacterial vaginosis against the climacteric syndrome - G.I. Reznichenko; N.Y. Reznichenko (Publishing House TRILIST, 2021)
Study objective: optimization of the treatment of climacteric syndrome (CS) and improvement of the life quality in women with bacterial vaginosis (BV) during menopause. Materials and methods. 58 women with natural menopause were examined, 38 of whom were diagnosed with BV. To correct the CS patient used the drug 17β-estradiol Divigel transdermal in combination with micronized progesterone orally. Patients with BV were divided into 2 subgroups: 15 women received standard treatment with metronidazole gel (comparison subgroup), 23 women additionally used Lactagel (main subgroup). The control group included 20 patients with CS without BV. The severity of CS was assessed with MRS scale. Microscopic and bacteriological examination of vaginal discharge was performed to determine the infectious agent, and the species composition of pathogens was determined with a polymerase chain reaction. BV was diagnosed according to Amsel criteria. CQLS questionnaire was used to assess the quality of life of patients with BV. The treatment effectiveness was assessed after 1 and 3 months from the start of treatment. Results. Divigel in women with uterus in combination with oral micronized progesterone has shown high efficiency in the CS correction within a month from the start of treatment. The most significant was the decrease in neurovegetative and psychoemotional symptoms after 3 months from the start of treatment. Lactagel in the therapy of patients with BV on the background of CS allowed increasing the lactobacilli content to the value in patients without BV, restoring the normal vaginal biotope and preventing of the disease recurrence, in contrast to the subgroup of patients who received standard treatment. Lactagel made it possible to improve the life quality of patients to an average level and to increase the overall level of life satisfaction, in contrast to the subgroup with standard treatment where these levels have remained low. Conclusions. Developed approaches to menopausal hormone therapy and BV therapy against the background of natural menopause allows optimizing treatment, improving the life quality of patients, which allows recommending them for widespread use in clinical practice.